Space-use and nest selection of southern flying squirrels (Glaucomys volans) at the edge of their geographic range - Bernhardt, Brandon (My University, 2025)
Southern flying squirrels (Glaucomys volans, hereafter “flying squirrels”) are common throughout the eastern United States, with the western edge of their geographic range extending into the Great Plains where deciduous forest transitions into grassland. Studies have documented flying squirrel space-use patterns and nest selection within the core of their range, though it is unclear if these patterns persist along their western range edge. I used VHF radiocollars to track 10 flying squirrels (six males, four females) in southeastern Kansas, USA to estimate home-range sizes and identify local-scale patterns in nest-site and nest-tree selection during summer and winter 2024. Flying squirrels had a mean home-range size of 1.55 ha (male = 1.56 ha, female = 1.54 ha) for 95% minimum convex polygon and 5.44 ha (male = 6.44 ha, female = 3.94 ha) for 95% kernel density estimate. Flying squirrels selected nest sites based on tree richness (number of unique genera of trees) and diameter at breast height (DBH). Greater tree richness and average tree DBH increased probability of local-scale habitat use. Flying squirrels selected nest-trees based on tree type (hard mast-producing tree or non-hard mast-producing trees) and DBH. Non-hard mast-producing trees and greater tree DBH showed increased probability of nest-tree use. Based on my results, I recommend that forest diversity in Kansas should be maintained, while allowing hard mast-producing trees to reach full maturity and retaining snags when faster developing trees die. This would allow large diameter and mature trees of many different species to persist without disturbance to quality nesting habitat for flying squirrels.
Keywords: Southern flying squirrel; Space-use; Home-range; Nest selection; Periphery population